Taxonomic differentiation of Cupressus sempervirens and C. atlantica based on morphometric evidence. Issue 5 (2nd September 2016) - Sękiewicz, Katarzyna; Boratyńska, Krystyna; Dagher-kharrat, Magda Bou; Ok, Tolga; Boratyński, Adam
Abstract : We investigated the interspecific morphological relationships of two related Mediterranean Cupressus taxa and the possible geographic differentiation of Eastern Mediterranean C. sempervirens using morphometric analysis. A total of 446 individuals, representing eight C. atlantica (Morocco) and 10 C. sempervirens (Greece, Turkey and Lebanon) populations were examined. The 17 morphological characters of cone, seed and shoot with leaves were measured and analysed statistically. Significant morphological differences between C. atlantica and C. sempervirens were detected for the majority of analysed characters. For C. sempervirens, significant differences were also detected and these were related to its three regions of origin, the Greek Islands, Taurus Mts and Lebanon Mts. Multivariate analyses did not indicate a clear geographic pattern of differentiation in C. sempervirens populations . A relatively low level of phenotypic differentiation was detected between populations originating from the Greek Islands and Taurus Mts. We also observed a moderate multivariate differentiation between the Lebanese and remaining C. sempervirens populations. Phenotypic differentiation detected in the Asian part of the C. sempervirens range reflects patterns of differentiation similar to those described for other taxa occurring in the Taurus and Lebanon Mts.